2021
DOI: 10.1186/s40164-021-00210-9
|View full text |Cite|
|
Sign up to set email alerts
|

Tregs and GvHD prevention by extracorporeal photopheresis: observations from a clinical trial

Abstract: The aim of the present study was to evaluate the circulating T regulatory cells (Tregs) in patients undergoing extracorporeal photopheresis (ECP) for the prevention of chronic graft-versus-host disease (GvHD) and to search for any correlation between Tregs counts and chronic GvHD occurrence. Among n = 12 patients with complete longitudinal data, the median cumulative values of absolute peripheral Tregs counts were 21.64 and 63.49 cells/µL for patients who developed chronic GvHD and those who did not develop it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In different cytokine environments, CD4 + T cells can differentiate into different subpopulations, including Th1, Th2, Th17 and Treg cells. Th1 and Th17 cells can contribute to aGVHD development, while Tregs can protect against aGVHD [51]. Interestingly, hUC-EVs-ATO reduced the frequency of Th1 and Th17 cells while increasing the Treg cell frequency in vivo but not in vitro.…”
Section: Discussionmentioning
confidence: 95%
“…In different cytokine environments, CD4 + T cells can differentiate into different subpopulations, including Th1, Th2, Th17 and Treg cells. Th1 and Th17 cells can contribute to aGVHD development, while Tregs can protect against aGVHD [51]. Interestingly, hUC-EVs-ATO reduced the frequency of Th1 and Th17 cells while increasing the Treg cell frequency in vivo but not in vitro.…”
Section: Discussionmentioning
confidence: 95%
“…ECP has exhibited therapeutic efficacy in the management of T cell-mediated diseases, particularly among the patients with GVHD, transplant rejections, and various autoimmune diseases. In murine models of GVHD, as well as in a majority of patients with GVHD, Tregs have been observed to proliferate in response to ECP [ 12 , 49 ]. On the other hand, in some clinical trials focusing on systemic sclerosis undergoing ECP, in addition to the increase of Tregs in the peripheral blood of the patients, it was also observed that Th17 cells, which had a surge at the beginning of the disease, were decreased after ECP treatment and positively correlated with the improvement of skin symptoms [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…ECP has demonstrated effective and safe therapeutic outcomes in the clinical management of various T cell-mediated disorders [ 10 , 11 ]. For instance, in patients with graft-versus-host disease (GVHD) or solid organ transplant rejection, the prophylactic or therapeutic use of ECP has shown specific and long-term immunosuppressive effects [ 12 15 ]. Moreover, prospective studies conducted on ECP treatment for other autoimmune disease like systemic sclerosis, Crohn’s disease, and type 1 diabetes, pemphigus vulgaris and other autoimmune diseases, have also revealed promising results [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the type of apoptosis induced in leukemic malignant T cells has not been further evaluated, in 8-MOP treated melanoma cell lines, photoactivation induced an immunogenic cell death ( 176 ). While ECP has been shown to eliminate alloreactive T cells in GVHD, it has also been reported to induce the generation of Tregs, a potentially unfavorable immune response in CTCL ( 177 ). Understanding the effect of ECP on Treg populations in CTCL in the past has been challenging given the difficulty of distinguishing malignant T cells expressing Treg markers from benign Tregs ( 178 ).…”
Section: Radiationmentioning
confidence: 99%